A rationally thin composite membrane with differentiated pore structure for industrial-scale alkaline water electrolysis - Jian You; Jinyu Lu; Chuanli Liu; Wei Wang; Yongzhao Li; Yuanzhong Gao; Longmin Liu; Xiangbo Luo; Xiaojun Bao; Huaiyin Chen; Jianying Huang; Yuekun Lai; et al. (Nature Communications)
Abstract Alkaline water electrolysis is one of the most prospective technologies for large-scale production of green hydrogen. Nevertheless, current porous membranes face the problem of weak ion transport or poor gas barrier performance. Here, we demonstrate a facile yet massive two-step casting and phase separation strategy to design a thin, asymmetric pore-structure modulated composite membrane for efficient, safe, and industrial-grade alkaline water electrolysis. The prepared composite membrane shows better electrolytic performance (1.71 V at 1 A cm−2) and stability (working for 6352 h). In addition, an industrial-grade electrolyzer equipped with composite membranes exhibits higher hydrogen production efficiency (1.03 Nm3·h−1), H2 purity (99.9%), and faster dynamic response (less than 20 min) compared to mainstream commercial membranes. Ultimately, we propose a semi-empirical model based on the operational characteristics of an electrolyzer equipped with composite membranes and predicting its matching behavior with dynamic renewable energy sources. This work explores the viability of manufacturing high-performance alkaline water electrolysis membranes for green hydrogen production under industrial conditions.